2003
DOI: 10.1095/biolreprod.102.005512
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Progesterone, Follistatin, and Follicle-Stimulating Hormone in Peripheral Plasma Across the Estrous Cycle and Pregnancy in Merino Ewes That Are Homozygous or Noncarriers of the Booroola Gene1

Abstract: The circulating concentrations of progesterone, FSH, and follistatin across the estrous cycle and gestation were compared in Australian merino sheep that were homozygous for the Booroola gene, FecB, or were noncarriers. The Booroola phenotype is due to a point mutation in the bone morphogenetic protein receptor 1B. Progesterone concentrations began to rise earlier and were higher in the Booroola ewes than in the noncarriers on most days of the luteal phase but not during the follicular phase of the cycle. Foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…These results support the notion that BMPs exert dual functions within the ovary, potentially increasing rate of PGC formation and follicle recruitment, while also inhibiting progesterone formation and follicular maturation required for ovulation. BMPs also clearly have a role in the pituitary regulating gonadotrophin release particularly FSH (McNatty et al 1989, Xia et al 2003, thus when BMP signalling is attenuated FSH concentrations rise. This in turn stimulates a precocious maturation of multiple smaller follicles, hence multiple ovulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results support the notion that BMPs exert dual functions within the ovary, potentially increasing rate of PGC formation and follicle recruitment, while also inhibiting progesterone formation and follicular maturation required for ovulation. BMPs also clearly have a role in the pituitary regulating gonadotrophin release particularly FSH (McNatty et al 1989, Xia et al 2003, thus when BMP signalling is attenuated FSH concentrations rise. This in turn stimulates a precocious maturation of multiple smaller follicles, hence multiple ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…The assay was performed using a similar procedure to that was described by Xia et al (2003). Briefly, the antiserum was Any follicle falling within the counting frame and not intersecting these two forbidden lines was counted, while others were not counted.…”
Section: Ria Of Progesteronementioning
confidence: 99%
See 1 more Smart Citation
“…The cellular mechanism responsible for this increase, however, has not been revealed (Mulsant et al 2001, Souza et al 2001, Wilson et al 2001, Campbell et al 2003, Crawford et al 2011. Evidence from our previous findings in BB sheep has shown that the attenuation of BMP signaling produces elevated FSH levels, and the initial number of primordial follicles are reduced; yet the rate of recruitment of primary follicles is substantially lower and results in a greater retention of the ovarian reserve in the mature ewe (Xia et al 2003, Ruoss et al 2009). Given that FSHRs are not expressed in primordial follicles, it is unlikely that FSH plays a role in this initial recruitment (Ruoss et al 2009).…”
Section: Introductionmentioning
confidence: 91%
“…However, it has been reported that BMPs inhibit the gonadotrophin-induced progesterone production by maturing follicles (Xia et al 2003, Pierre et al 2004, McNatty et al 2007, in addition to its inhibitory action on final cell differentiation (Cejalvo et al 2007),…”
Section: The Role Of Bmps In Ovarian Functionmentioning
confidence: 99%